Pelabelan Total Super (a,d)-Sisi Antimagic Pada Graf Buah Naga - Nurvitaningrum, Agnes Ika; Dafik, Dafik; Setiawani, Susi (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph $G$ is called an $(a,d)$-edge-antimagic total labeling if there exist a one-to-one mapping $f : f(V)={1,2,3,...,p} o f(E)={1,2,dots,p+q}$ such that the edge-weights, $w(uv)=f(u)+f(v)+f(uv), uv in E(G)$, form an arithmetic progression ${a,a+d,a+2d,dots,a+(q-1)d}$, where $a>0$ and $dge 0$ are two fixed integers, form an arithmetic sequence with first term $a$ and common difference $d$. Such a graph $G$ is called {it super} if the smallest possible labels appear on the vertices. In this paper we recite super $(a,d)$-edge-antimagic total labelling of connectedÂ  Dragon Fruit Graph. The result shows that Dragon Fruit Graph have a super edge antimagic totalÂ  labeling for $din{0,1,2}$.